Quaternary prevention against the excesses of medicine (Portuguese Journal of Family Medicine and General Practice, 2007)
QUATERNARY PREVENTION AGAINST EXCESSIVE MEDICAL INTERVENTION Medicine can be potential harmful for patients, because of the danger of over diagnosis, therapeutic/preventive excess, causing unnecessary medical intervention. Quaternary prevention is a new concept in preventive medicine, whose objective is to avoid and control these perverse effects. In this paper we describe strategies to identify the most common causes of unnecessary medical intervention and measures to ensure quaternary prevention, in order to provide the best quality care for the patients.
Keywords: Quaternary Prevention; Clinical Epidemiology